Freezing-tolerant and robust gelatin-based supramolecular conductive hydrogels with double-network structure for wearable sensors - Jia Yang (Elsevier, 2021)
It is significant to design stretchable conductive hydrogels with high integrated mechanical and excellent anti-freezing performances for broadening their application fields. Herein, a freezing-tolerant and robust poly(N-hydroxymethyl acrylamide)/gelatin/glycerol supramolecular conductive hydrogel with double networks is synthesized via an one-pot method, where poly(N-hydroxymethyl acrylamide) can self-cross-link, and also interact with gelatin. Glycerol endows the conductive hydrogel with anti-freezing property in mechanics and electricity, and can also interact with poly(N-hydroxymethyl acrylamide) and gelatin to further enhance mechanical properties. Under optimal conditions, the conductive hydrogel exhibits high strength, super extensibility, rapid self-recovery, excellent fatigue resistance and high ionic conductivity. It possesses temperature insensitivity of mechanical properties and weak dependence of electrical behaviors on temperature. Furthermore, it exhibits excellent anti-freezing resistance response to strain, and can as sensor detect human activities. Thus, this work provides a simple and promising strategy for designing stretchable conductive gels with integrated high performances aiming for wearable intelligent electronics.